Economic Evaluations on Antimicrobial Stewardship Programme: A Systematic Review - Nor Haizan Ibrahim; Khalidah Maruan; Hasryn Azzuar Mohd Khairy; Yet Hoi Hong; Ahmad Fauzi Dali; Chin Fen Neoh (Frontiers Media S.A., 2018)
Purpose: To systematically review studies on cost-effectiveness of implementing Antimicrobial stewardship programmes (ASP) in the hospital setting. Methods: A systematic literature search was performed using electronic databases, such as EMBASE, PubMed/Medline, CINAHL, NHS and CEA Registry from 2000 until 2017. The quality of each included study was assessed using Joanna Briggs Institute Critical Appraisal Checklist for Economic Evaluations and Consolidated Health Economic Evaluation Reporting Standards Statement checklist. Results: Of the 313 papers retrieved, five papers were included in this review after assessment for eligibility. The majority of the studies were cost-effectiveness studies, comparing ASP to standard care. Four included economic studies were conducted from the provider (hospital) perspective while the other study was from payer (National Health System) perspective. The cost included for economic analysis were as following: personnel costs, warded cost, medical costs, procedure costs and other costs. Conclusions: All studies were generally well-conducted with relatively good quality of reporting. Implementing ASP in the hospital setting may be cost-effective. However, comprehensive cost-effectiveness data for ASP remain relatively scant, underlining the need for more prospective clinical and epidemiological studies to incorporate robust economic analyses into clinical decisions.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.